2006 International Conference on Image Processing 2006
DOI: 10.1109/icip.2006.312411
|View full text |Cite
|
Sign up to set email alerts
|

Low Cost Robust Blur Estimator

Abstract: A novel local blur estimation method is presented in the paper. Focal blur process is usually modeled as a Gaussian low-pass filtering and then the problem of blur estimation is to identify the Gaussian blur kernel. In the proposed method, the input blurred image first is re-blurred by Gaussian blur kernels with different blur radii. Then the difference ratios between the multiple re-blurred images and the input image are used to determine the unknown blur radius. We show that the proposed method does not requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 7 publications
0
61
0
Order By: Relevance
“…Other terms are spike noise, random noise or independent noise. Black and white dots appear in the image explained in [5] as a result of this noise and hence salt and pepper noise. This noise arises in the image because of sharp and sudden changes of the image signal.…”
Section: Restoration Techniques 31 Noise Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other terms are spike noise, random noise or independent noise. Black and white dots appear in the image explained in [5] as a result of this noise and hence salt and pepper noise. This noise arises in the image because of sharp and sudden changes of the image signal.…”
Section: Restoration Techniques 31 Noise Modelsmentioning
confidence: 99%
“…The idea of image restoration is to minimize the noise [5,2] and blurring image [4,2] from a degraded image by various atmospheric defects. It introduces an effective method for image restoration is de-convolution based on a coefficient of image formulated in the wavelet domain wavelet based denoising of an image can be done since Donoho in [9].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the existing works perform blind image deconvolution based on a single image [15]. A PSF is inferred through total variation regularization [16], the variation of Gaussian scale in the edges [17][18] [19], or variation in the wavelet domain [20] [21]. Recently, M. Nishiyama [6] has revealed that deblurring from a single image is an ill-posed problem and these deblurring methods are insufficient for accurate face recognition.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed method adopts a simple non-iterative blur estimator, as proposed in our earlier work [4]. The blur estimator uses a Gaussian isotropic PSF model and the difference between digitally re-blurred versions of an image is used to estimate the blur radius without edge detection.…”
Section: Introductionmentioning
confidence: 99%